2001
DOI: 10.1002/jbm.1265
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation of rat calvarial osteoblasts on type I collagen‐coated titanium alloy

Abstract: Several attempts have been made to improve osseointegration of titanium alloy as an implant material by modification of its surface. In the present study, proliferation, differentiation, and mineralization of osteoblasts on type I collagen-coated Ti6Al4V were investigated. The activity of alkaline phosphatase and the accumulation of calcium by osteoblasts grown on titanium alloy were significantly higher compared to cells grown on polystyrene. Precoating of the implant surface with type I collagen did not exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 36 publications
(41 reference statements)
9
70
0
8
Order By: Relevance
“…This includes an early differentiation phase characterized by expression and synthesis of ECM components, followed by ECM maturation and ending with mineralization of the ECM (74,75). Therefore, primary hBMSC served as a cellular model and were differentiated into osteoblasts by the use of an osteogenic medium.…”
Section: Comparison Of the Matrix Vesicle Proteome With Hbmsc Proteomementioning
confidence: 99%
“…This includes an early differentiation phase characterized by expression and synthesis of ECM components, followed by ECM maturation and ending with mineralization of the ECM (74,75). Therefore, primary hBMSC served as a cellular model and were differentiated into osteoblasts by the use of an osteogenic medium.…”
Section: Comparison Of the Matrix Vesicle Proteome With Hbmsc Proteomementioning
confidence: 99%
“…Next, we tested whether implant coating with components of the bone extracellular matrix (ECM) would stimulate bone osseointegration in our compromised setting (Stadlinger et al, 2009a). Collagen type I is the main structural component of the bone organic ECM and has been previously demonstrated to favour the adhesion of osteoblastic cells (Becker et al, 2002). In addition, the application of glycosaminoglycans such as chondroitin sulphate (CS) influences the adhesion, proliferation and differentiation of osteoblasts (Bierbaum et al, 2006; Douglas et al, 2007).…”
Section: B Stadlinger Et Al Modified Implants In An Osteoporosis Modelmentioning
confidence: 99%
“…In the present study, growth analysis by MTT assay and total protein content revealed differences between Col-Ti and M-Ti only at day 3, therefore during (Becker et al 2002). Based on our results using human alveolar bonederived cells, we speculate that Col-Ti surface obtained by plasma deposition-acrylic acid grafting may accelerate cell cycle dynamics only at the first periods of the proliferative phase of the cultures.…”
Section: Discussionsupporting
confidence: 57%